2015
DOI: 10.1371/journal.pone.0123473
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Characterization of a Plasmodium Liver Stage-Specific Promoter

Abstract: Little is known about stage-specific gene regulation in Plasmodium parasites, in particular the liver stage of development. We have previously described in the Plasmodium berghei rodent model, a liver stage-specific (lisp2) gene promoter region, in vitro. Using a dual luminescence system, we now confirm the stage specificity of this promoter region also in vivo. Furthermore, by substitution and deletion analyses we have extended our in vitro characterization of important elements within the promoter region. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Why expression of sbp1 and mahrp1a and mahrp1b appears to be lower in EF stage merozoites than in EEF stage merozoites is unknown. One reason might be, that in course of EF stage infection, the spleen is heavily remodeled (63–65) and allows for passage of infected RBC, making an efficient sequestration and thus a pronounced expression of sequestration ligands on the surface of the infected RBC less necessary (50). The parasite might thus be less dependent on intense trafficking of sequestration ligands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Why expression of sbp1 and mahrp1a and mahrp1b appears to be lower in EF stage merozoites than in EEF stage merozoites is unknown. One reason might be, that in course of EF stage infection, the spleen is heavily remodeled (63–65) and allows for passage of infected RBC, making an efficient sequestration and thus a pronounced expression of sequestration ligands on the surface of the infected RBC less necessary (50). The parasite might thus be less dependent on intense trafficking of sequestration ligands.…”
Section: Resultsmentioning
confidence: 99%
“…6 ). The genes lisp1 (PBANKA_1024600) and lisp2 (PBANKA_1003000) have been previously reported to be expressed exclusively during EEF stage development (6567). This is clearly reflected by our RNA-seq analysis where substantial lisp1 and lisp2 mRNA levels were only found in EEF stages, from 24hpi to DC.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the uis4 (upregulated in infectious sporozoites) gene is specifically upregulated in infectious sporozoites, those resident in the salivary glands of the mosquitoes and named accordingly [ 32 34 ]. Lastly, the lisp2 gene, encoding the liver stage-specific protein 2, is expressed exclusively during late liver stage development prior to formation of infectious merozoites, the parasite forms infecting red blood cells [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…These studies also determined that LISP2, named after its expression pattern comparable with LISP1 (Tarun et al, 2008), is exclusively expressed in the mid-to-late liver stages stages. Another group has independently confirmed these results by characterizing stage-specific expression using the promoter region of P. berghei LISP2, in conjunction with a dual luminescence system (Helm et al, 2010; De Niz et al, 2015). Immunofluorescence assays of liver stages showed that LISP2 is transported to the vacuolar space and then, after processing, exported into the hepatocyte cytoplasm (Orito et al, 2013; Itani et al, 2014).…”
Section: 6-cys Proteins In the Pre-erythrocytic Stagesmentioning
confidence: 88%